Illuminating affects: Sexual violence as a crime against humanity. The Argentine case - Macon, Cecilia (Historein, 2013)
This paper analyses testimonies of sexual violence provided in the context of the current trials in Argentina for crimes against humanity, in order to assess the role played by affects, both in historical representation and in the constitution of agency. Regarding these matters, it is important to stress that the concept of victimisation has been analyzed within the framework of gender theories in radical opposition to that of agency: the passiveness of the injury vis-à-vis the power of the action. It is my understanding that, throughout the analysis of what I call “metatestimonies”, meaning what victims express about their experiences of giving testimony, lies the possibility of challenging such a dichotomy. This is particularly the case when these metatestimonies are scrutinised under the scope of affects. My field research, based on interviews with testifiers and on observations of the trials, seeks to contradict observations that sustain that these testimonies victimise women twice by having them re-enact their trauma.